PERBEDAAN MORALITAS SISWA YANG MENGGUNAKAN METODE SIMULASI DAN PROBLEM SOLVING - Dwi Oktaviani Ogara; Eddy Purnomo; Nurdin Nurdin (JEE (Jurnal Edukasi Ekobis), 2013)
The method which used in this research is comparative study with experimental approaches. The study population totaled 313 students with a total sample of 74 students.Hypotheses of test using two-way analysis of variance formula and the t-test two independent samples.Based on the analysisof dataobtainedthe following research findings, (1) there is a difference of student morality in learning of IPS between students who are learning using simulation and problem solving. (2) there are differentiation of morality in the learning of IPS between students who have intrapersonalwith interpersonal intelligence. (3) there is no interaction between learning method with intrapersonal and interpersonal student in the learning of IPS. (4) students morality in learning of IPS which is using simulation is higher than problem solving on students who have intrapersonal intelligence. (5) students morality in learning of IPS which is using simulation is higher than problem solving on students who have interpersonal intelligence. (6) students morality in learning of  IPS which have the intrapersonal intelligence is lower than the interpersonal intelligence in simulation. (7) students morality in learning of IPS which have the intrapersonal is lower than the interpersonal by using problem solving. Kata kunci: moralitas, simulasi, ps, intrapersonal, interpersonal.